Glasgow Outcome Scale Assessment in Patients with Cerebral Toxoplasmosis - Brigitta Berlianty; Sofiati Dian; Ahmad Rizal Ganiem (Althea Medical Journal, 2022)
Background: Cerebral toxoplasmosis is a Toxoplasma gondii infection affecting the brain. Assessment of the functional outcome after treatment is needed as an evaluation for therapeutic management. One of the instruments used is the Glasgow Outcome Scale (GOS). This study aimed to assess the functional outcome of cerebral toxoplasmosis patients using GOS.Methods: A Cross-sectional descriptive study with total sampling method was conducted. Medical records were retrieved from patients with cerebral toxoplasmosis registered at the Department of Neurology, Dr. Hasan Sadikin General Hospital, Bandung during year 2017–2019. Inclusion criteria were patients with cerebral toxoplasmosis aged >18 years and had a positive HIV serological test. The GOS was assessed and presented in frequency, using Microsoft Excel and SPSS software ver. 25.0.Results: Of 87 patients, 68% had somnolent on admission to the hospital, 51% had hemiparesis/hemiplegia, and 76% had GOS 3, indicating severe disability. Almost one third (28%) of patients died during hospitalization with non-neurological complications as the most common cause of death (63%). On discharge from the hospital, 82% of the survivors were fully alert, 40% had hemiparesis/hemiplegia, and 33% had GOS 4 (mild disability).Conclusions: Most of the cerebral toxoplasmosis patients come to the hospital with severe disability. During the treatment, one third of patients died, and those who survived had mild disability. GOS has improved after hospitalization, suggesting that GOS is useful for assessment of therapeutic management.